Prevalence of Developmental Coordination Disorder signs in children 5 to 14 years in São Carlos - Barba,Patricia Carla de Souza Della (2017)
This study aimed to identify the prevalence of Developmental Coordination Disorder (DCD) in children aged 5-14 years, enrolled in public preschools and elementary schools in São Carlos - SP. There were 130 participating families. Instruments were: Developmental Coordination Disorder Questionnaire - Brazil (DCDQ - Brazil), Brazil criteria and a questionnaire for the characterization of children. The prevalence of DCD found was 30%, which is overestimated when compared to data found in much of the literature, justified by the use of the instrument for detection of the DCD. No significant difference was found between the presence of signs in boys and girls and there was a higher concentration of children with DCD signs on B2, C1 and C2 socioeconomic classes. The prevalence of DCD signs was higher in children over 8 years.